Pemeriksaan Kesehatan dan Edukasi Gangguan Neurologi sebagai Upaya Deteksi Dini dan Pencegahan Penyakit Saraf pada Masyarakat - Anak Agung, Padmiswari; Nadya Treesna Wulansari; Kadek Buja Harditya (LOSARI DIGITAL, 2025)
Neurological disorders are a major cause of disability worldwide, yet public awareness of early prevention remains low. This community service program aimed to improve knowledge and awareness of neurological health through education and screening activities in Guwang Village, Gianyar Regency. Fifty community members participated in blood pressure checks, reflex and coordination tests, and educational sessions on neurological disease prevention. The program was carried out in three stages: preparation, implementation, and evaluation. Results showed that 36% of participants had hypertension and 22% showed mild neurological symptoms. Post-education assessments revealed a 30.8% increase in knowledge, indicating improved awareness and preventive behavior. This program effectively strengthened community understanding of neurological health and encouraged early detection efforts.